2021
DOI: 10.3389/fpsyg.2021.729543
|View full text |Cite
|
Sign up to set email alerts
|

How Do People Cope During the COVID-19 Pandemic and Stay Well? A Salutogenic Longitudinal Study in Israel

Abstract: Employing the salutogenic approach, this longitudinal study explored the effects of coping with the COVID-19 pandemic in Israel, as it evolved from an acute to a chronic stress situation, during the first year. We examined the role of individual [sense of coherence (SOC)], social (perceived social support), and national [sense of national coherence (SONC)] coping resources, as well as situational and demographic factors, in predicting mental health and anxiety. Data was collected in five phases between March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The final outcome of coping with stress depends on various individual and external factors. While some of them, such as optimism or self-esteem, cannot be rapidly and easily targeted, research highlights the impact of others with the example of social support also in the circumstances of the global pandemic [ 30 , 33 , 34 , 35 ]. While the pandemic-related restrictions largely reduced access to social interactions and, therefore, social support increasing the risk of worsened mental health, the impact on the population of chronically-ill patients was even more deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…The final outcome of coping with stress depends on various individual and external factors. While some of them, such as optimism or self-esteem, cannot be rapidly and easily targeted, research highlights the impact of others with the example of social support also in the circumstances of the global pandemic [ 30 , 33 , 34 , 35 ]. While the pandemic-related restrictions largely reduced access to social interactions and, therefore, social support increasing the risk of worsened mental health, the impact on the population of chronically-ill patients was even more deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…Also, high SoC was significantly associated with a sufficient level of psychological well-being, none/one psychosomatic complaint, and low FA among all students, which was in line with the available literature. Mana et al ( Mana et al , 2021b ) have shown a strong association between SoC and psychological well-being during the COVID-19 pandemic among seven countries despite their socio-cultural differences. In two recent studies, Dodd et al ( Dodd et al , 2021 ) found a significant association between SoC and well-being among university students in Australia, and Dadaczynski et al ( Dadaczynski et al , 2021a ) have illustrated the association of the subdimensions of SoC, namely comprehensibility, meaningfulness, and manageability with psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…SOC levels remained stable while the other coping resources levels gradually decreased. Strong correlations were found between the level of SOC at the outbreak of the pandemic and the mental health level after a year of COVID-19 crisis (Mana et al, 2021c).…”
Section: Main Findings Of the Longitudinal Study In Israelmentioning
confidence: 93%